Ensuring Pesticide Compatibility in Tank Mixes: PI301, 9/2024 - Bultemeier, Brett; Carter, Ethan; Sperry, Benjamin (EDIS, 2024)
This publication is intended to help pesticide applicators and county Extension faculty to better understand proper pesticide mixing and to reduce instances of incompatibility. After reading this publication, readers should understand the causes of pesticide incompatibility, how to avoid incompatibility, and how to maximize the benefits of tank mixing. Written by Brett Bultemeier, Ethan Carter, and Benjamin Sperry, and published by the UF/IFAS Pesticide Information Office, September 2024.